2016
DOI: 10.1155/2016/4385312
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Real-Time Continuous Glucose Monitoring Use on Glucose Variability and Endothelial Function in Adolescents with Type 1 Diabetes: New Technology—New Possibility to Decrease Cardiovascular Risk?

Abstract: Children with type 1 diabetes (T1DM) are the high-risk group of accelerated atherosclerosis. Real-time continuous glucose monitoring (RT-CGM) provides possibilities for the detection of glycaemic variability, newly recognized cardiovascular risk factor. The aim of the study was to assess the usefulness of RT-CGM as an educational tool to find and reduce glycaemic variability in order to improve endothelial function in T1DM adolescents. Forty patients aged 14.6 years were recruited. The study was based on one-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…In a single group study Dal et al [32] found no effect of flexible insulin therapy designed to reduce glucose variability although mean amplitude glucose excursion also did not change. Jamiolkowska et al [40] found that reducing glucose variability improved endothelial function in adolescents with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…In a single group study Dal et al [32] found no effect of flexible insulin therapy designed to reduce glucose variability although mean amplitude glucose excursion also did not change. Jamiolkowska et al [40] found that reducing glucose variability improved endothelial function in adolescents with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous glucose monitoring ( associated with a negative impact on brain volume and growth [4], and markers of cardiovascular morbidity [5] in children with type 1 diabetes, despite short disease duration. The use of CGM can reduce GV in adults and youth with type 1 diabetes [6,7], however, this has not yet been proven in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Additional benefits of CGMS are reducing daily fluctuations of glucose levels. Thus, glycemic variability in type 1 DM patients using insulin pumps and real-time glucose monitoring devices had an SD reduction from 60.74 to 51.67 mg/dl (p=0.010), and AUC diminished from 41.23 to 21.22 (p<0.001) (35). Moreover, a recent study showed that integrated pump/CGMS technology versus multiple daily injections in T1DM increases life expectancy by 3.51 years (95% CI, 3.47-3.55) (36).…”
Section: Poc Continuous Glucose Monitoring Systems (Cgms) In Diabetesmentioning
confidence: 96%